Asserting the Diasporic Identity in Uma Parameswaran’s Oeuvre - Amrutha T V (The Creative Launcher, 2018)
Uma Parameswaran is a versatile writer-critic who has attempted to capture the trauma and dilemma of the diasporic self. Drawing on her first hand knowledge of the white collar, professional and academic diaspora in Canada, she attempts to voice their dilemmas and confusions, and above all, their feeling of rootlessness, their fear that having been uprooted once, they will never again be able to take root anywhere, despite their best efforts. The angst of the diaspora, striving to retain their identity even as they struggle to assimilate and become one of “them”, forms the core of Uma Parameswaran’s oeuvre. She has coined the term “saclit” to denote the literature produced by South Asian Canadian Diaspora, and has also written numerous critical essays on the subject. She explains: “The literature of Canadian writers born on the Indian subcontinent.... is varied in content and form, but common to all of them is a passionate faith in their own voice that is raised to express their Canadian experience” (SACLT 3)